Penerapan Pembelajaran Berbasis Proyek Pada Mata Pelajaran Ipas Kelas V Di SD Negeri 12 Peguyangan Denpasar - Ni Luh Putu Widya Bakti Cantiyani; Ni Made Anggreni; Kd Jayanthi Riva Prathiwi (Tampung Penyang, 2025)
In the Merdeka Curriculum, a reform has been introduced by integrating Science (IPA) and Social Studies (IPS) into a single subject called IPAS, which emphasizes contextual learning based on real-life experiences. One of the approaches used is Project Based Learning (PjBL), which actively engages students in completing projects to enhance their understanding and motivation to learn. Based on interviews with the fifth grade homeroom teacher, it was found that students often experience confusion and quickly forget the material, making the implementation of PjBL a relevant solution to address these issues in IPAS learning. This study discusses the following problems: (1). How is project based learning implemented in the IPAS subject for fifth grade students at SD Negeri 12 Peguyangan Denpasar, (2). What are the challenges in implementing project based learning in the IPAS subject for fifth grade students at the school, (3). What efforts are made to overcome these challenges in the implementation of project based learning. The theories used to address the above problems are behaviorist theory and constructivist theory. Data collection methods included observation, interviews, documentation, and literature study. The data analysis technique involved data reduction, data display, and drawing conclusions. The results of this study show that: (1). the implementation of project based learning at SD Negeri 12 Peguyangan Denpasar includes designing a project based learning model that requires structured steps to guide and give a clear picture to students throughout the learning process, (2). the challenges encountered in implementing project based learning include limited time, lack of active participation from all group members during discussions, and insufficient facilities for project development, (3). efforts to address these challenges include making early agreements on project planning and scheduling, encouraging collaboration and teamwork among group members, and bringing backup materials and tools.